2006
DOI: 10.4049/jimmunol.176.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Myeloid Cell Function through the CD200 Receptor

Abstract: Myeloid cells play pivotal roles in chronic inflammatory diseases through their broad proinflammatory, destructive, and remodeling capacities. CD200 is widely expressed on a variety of cell types, while the recently identified CD200R is expressed on myeloid cells and T cells. CD200 deletion in vivo results in myeloid cell dysregulation and enhanced susceptibility to autoimmune inflammation, suggesting that the CD200-CD200R interaction is involved in immune suppression. We demonstrate in this study that CD200R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
175
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(184 citation statements)
references
References 45 publications
8
175
0
1
Order By: Relevance
“…Conversely, RA SF abrogated the expression of CD163, even in the presence of the M2-polarizing factor IL-10 ( Figures 1A and B). These data were confirmed by the expression pattern of CD200R, an inhibitory macrophage receptor that is down-regulated during classic macrophage activation (16,17). The expression of CD200R was up-regulated by SpA SF but suppressed by maturation in the presence of RA SF ( Figure 1C).…”
Section: Resultssupporting
confidence: 62%
“…Conversely, RA SF abrogated the expression of CD163, even in the presence of the M2-polarizing factor IL-10 ( Figures 1A and B). These data were confirmed by the expression pattern of CD200R, an inhibitory macrophage receptor that is down-regulated during classic macrophage activation (16,17). The expression of CD200R was up-regulated by SpA SF but suppressed by maturation in the presence of RA SF ( Figure 1C).…”
Section: Resultssupporting
confidence: 62%
“…The cell population expressing the monocyte/macrophage marker CD14, which is usually taken for macrophages infiltrating AT, could be separated into two subpopulations: one negative in MR expression and one expressing MR to a very high extent (Figure 1a The phenotype of ATMs is M2-like and independent of AT location Flow cytometric determination of a large panel of M1 and M2 macrophage marker molecules revealed that, besides CD14 and MR, ATMs highly expressed the haemoglobin scavenger receptor CD163 and the integrin avb5 as well as considerable amounts of DC-Sign (CD209), a C-type lectin on macrophages, 22,23 and the anti-inflammatory signalling receptor OX-2 (CD200). 24 All these molecules were expressed on macrophages differentiated from PBM in vitro by culture with IL-4 (M2 (IL-4)) and/or IL-10 (M2 (IL-10)), but only at negligible amounts on M1 macrophages (Figure 2 and Table 1). We found no phenotypical difference in ATMs from different AT locations (Figure 2 Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, CD200R expression was reported on CD4 + T cells and triggering of CD200R on PBMC resulted in monocyte-mediated inhibition of tetanus toxoid-induced cytokine responses (Jenmalm et al, 2006). On dendritic epi-dermal T cells, CD200R crosslinking inhibited ␣CD3-induced proliferation and cytokine secretion (Rosenblum et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…In vitro studies have shown that ligation of CD200R results in decreased degranulation and cytokine secretion by mast cells, monocytes and macrophages (Jenmalm et al, 2006;Cherwinski et al, 2005). In addition, deletion of the CD200 gene in mice results in enhanced susceptibility to auto-immune disease and increased myeloid response to inflammation .…”
Section: E-mail Address: Lmeyaard@umcutrechtnl (L Meyaard)mentioning
confidence: 99%